Analysis of Routing Protocols based on Network parameters in Wanet - Sarao, Pushpender; Sindhu, P; Navakishor, V (International Journal of Computer Sciences and Engineering, 2025)
Ad-hoc networks are mostly used in each and every field of our daily life. There are so many circumstances in wireless ad-hoc networks, on which performance of networks depends. To achieve a better network performance, it is mandatory to identify the network circumstances and appropriate routing protocols. Routing protocols plays a vital role a routing process in ad-hoc networks. AODV (Ad-hoc on demand Distance Vector), DSR (Dynamic Source Routing), and DSDV (Destination-Sequenced Distance-Vector) are the well familiar routing protocols which are mostly used in mobile ad- hoc networks. In this paper, we analysed these routing protocols by considering several performance metrics like throughput, end-to-end delay, normalized routing load, received packets at various speeds and pause times